A Sequential Study of Virus Expression in Retrovirus-induced Arthritis of Goats - Klevjer-Anderson, Paula; Adams, D. Scott; Anderson, Lawrence W.; Banks, Keith L.; McGuire, Travis C. (Journal of General Virology, 1984)
SUMMARY Persistent infection by the retrovirus caprine arthritis-encephalitis virus (CAEV) induces arthritis in goats which closely resembles rheumatoid arthritis. To examine the relationship between virus expression and development of clinical disease, ten goat kids were inoculated with CAEV and examined at successive intervals through 18 months post-infection. Virus was monitored in cell-free synovial fluid cells, serum and peripheral blood cells by titration, co-cultivation and immunofluorescent techniques. Virus was readily recovered from the synovial cavity of all animals during the first 4 weeks of infection, followed by a reduction and fluctuation in virus titres and ability to detect virus. Recovery of CAEV from peripheral blood cells occurred at low frequency while viraemia was rare. Results obtained over a period of 18 months indicate a positive association between virus expression in the synovial cavity and development of clinically detectable disease.
Keywords: pathogenesis